1993
DOI: 10.1271/bbb.57.1638
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stability of Polyunsaturated Fatty Acids in an Aqueous Solution

Abstract: The relative oxidative stability of six kinds of typical polyunsaturated fatty acids (PUF As) was investigated in an aqueous solution (pH=7.4 at 37°C) with Fe 2 + -ascorbic acid as a catalyst. The highest stability was shown by docosahexaenoic acid (22: 6n-3, DHA), followed by eicosapentaenoic (20: 5n-3), arachidonic (20: 4n-6), «-linolenic (18: 3n-3), 'V-linolenic (18: 3n-6), and linoleic (18: 2n-6, LA) acids, indicating that the stability increased with increasing degree of unsaturation. The significant diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
84
1
2

Year Published

1994
1994
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 139 publications
(92 citation statements)
references
References 3 publications
5
84
1
2
Order By: Relevance
“…With respect to PV measurement, many researchers have agreed that linoleic and linolenic acids are oxidized much faster than oleate. But for those long-chain PUFAs, such as AA and DHA, they were found to have lower PV than linoleate in aqueous micelles and certain emulsions (22,24). In our case, since SL contained 56.6% linoleate while EL had only 16.2% linoleate ( Table 2), we would assume that SL had lower oxidative stability than EL.…”
Section: Resultsmentioning
confidence: 60%
“…With respect to PV measurement, many researchers have agreed that linoleic and linolenic acids are oxidized much faster than oleate. But for those long-chain PUFAs, such as AA and DHA, they were found to have lower PV than linoleate in aqueous micelles and certain emulsions (22,24). In our case, since SL contained 56.6% linoleate while EL had only 16.2% linoleate ( Table 2), we would assume that SL had lower oxidative stability than EL.…”
Section: Resultsmentioning
confidence: 60%
“…The oxidation rate of polyunsaturated fatty acids (PUFAs) is directly proportional to the number of bisallylic positions present in their mole cules.1 -6) Therefore, it is generally accepted that fish oils, containing high levels of n-3 PUFAs such as docosahex aenoic acid (DHA, 22:6n-3) and eicosapentaenoic acid (EPA, 20:5n-3), are highly susceptible to autoxidation.5,7) However, these results have been mainly obtained by au toxidation of the purified substrate itself in air. In our pre vious paper, 8) we demonstrated that the oxidative stability of PUFA in an aqueous system is different from that in the neat phase and that DHA and EPA are oxidatively more stable than linoleic acid in an aqueous solution.…”
mentioning
confidence: 88%
“…However, the levels fluctuated in the samples, probably owing to the instability of the hydroperoxides, which has been observed in rat liver microsomes. 31) There were no significant differences in the increase in these hydroperoxides between the two diet groups. The TBARS levels in unoxidized hepatocytes in both diet groups were similarly low, and increased with oxidation due to ADP/Fe(II) ion and hydrogen peroxide (Fig.…”
Section: Resultsmentioning
confidence: 83%